Dnevnik IX Vneocherednogo s"ezda narodnykh deputatov Rossiiskoi Federatsii . Dnevnik IX Vneocherednogo s"ezda narodnykh deputatov Rossiiskoi Federatsii . Diary of the 9th Extraordinary Congress of People's Deputies of the Russian Federation . Дневник IX Внеочередного съезда народных депутатов Российской Федерации - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. People's Deputies discuss the decrees of the President of the Russian Federation. Featured in the program: Popov, Aleskandr (People's Deputy); Sokolov, Veniamin (People's Deputy); Anichkin, Ivan (People's Deputy) Contributors: Tolstykh, Evgenii (Anchor) Народные депутаты обсуждают указы президента Российской Федерации. В программе участвуют: Попов, Алескандр (Народный депутат); Соколов, Вениамин (Народный депутат); Аничкин, Иван (Народный депутат) Создатели: Толстых, Евгений (Ведущий/Ведущая)